A method for preparing modified NdFeB magnetic powder
Through the preparation method of modified NdFeB magnetic powder, the dispersion reaction between nanometal powder and solvent is used, combined with ultrasonic dispersion and stirring technology, a cladding layer is formed, which solves the problem of insufficient performance of existing NdFeB magnetic powder and achieves high residual performance Permanent magnets of magnetism, magnetic energy accumulation and coercive force.
Patent Information
- Application Number
- CN202211235006.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-10
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-10-10
AI Technical Summary
The NdFeB magnetic powder used in existing industrial motors has not been modified, resulting in the relatively small residual magnetic and magnetic energy accumulation of the permanent magnet, low coercive force, and large magnetic reduction rate, which cannot meet the needs of high-performance industrial motors.
After dispersing the nano-NdFeB magnetic powder with the nano-metal powder and solvent, adding concentrated ammonia water and tetraethyl orthosilicate, the first and second modified NdFeB magnetic powder were prepared, and the modification was made by ultrasonic dispersion and stirring. The protease agent and the magnetic powder are connected through chemical bonds to form a cladding layer to improve magnetic properties.
It significantly improves the residual magnetic and magnetic energy product of permanent magnets, enhances coercive force, and reduces the magnetic reduction rate, meeting the demand for high-performance magnets in industrial motors.
Abstract
Description
Technical Field
[0001] The invention relates to the field of NdFeB magnetic powder technology, in particular to a preparation method of modified NdFeB magnetic powder. Background Art
[0002] The magnets used in motors directly affect the life, reliability and durability of the motors. The main raw materials of motor magnets are generally permanent ferrites, and rare earth permanent magnet materials are also used. The basic performance of permanent magnets used in motor vehicles is mainly reflected in two indicators. One is the magnetic energy product (BH). max , and the other is intrinsic coercivity (Hcj). With the development of science and technology in the field of magnetic material applications, the performance requirements for high-performance industrial motors have been further improved. Industrial motors not only require high magnetic energy product, but also high intrinsic coercivity to suppress the demagnetization effect caused by the reverse electromagnetic field caused by temperature changes and large current shocks. Therefore, it is a very important issue to ensure the stability and reliability of industrial motors during long-term use.
[0003] At present, permanent magnets for industrial motors are mainly made of NdFeB magnetic powders, which are usually not modified, resulting in small remanence and magnetic energy product, low coercivity, and large demagnetization rate of the permanent magnets produced, which cannot meet the needs of use. Therefore, it is necessary to study a solution to solve the above problems. Summary of the invention
[0004] In view of this, the present invention aims to address the deficiencies in the prior art, and its main purpose is to provide a method for preparing modified NdFeB magnetic powder, which can increase the remanence and magnetic energy product of the permanent magnet, while improving the coercive force and reducing the demagnetization rate.
[0005] To achieve the above purpose, the present invention adopts the following technical solutions:
[0006] A method for preparing modified NdFeB magnetic powder comprises the following steps:
[0007] (1) dispersing a first nano-NdFeB magnetic powder, a nano-silver powder and a nano-aluminum powder in a first solvent, adding a first concentrated ammonia solution and a first tetraethyl orthosilicate to react, thereby obtaining a first modified NdFeB magnetic powder;
[0008] (2) dispersing a second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in a second solvent, adding a second concentrated ammonia solution and a second tetraethyl orthosilicate to react, thereby obtaining a second modified NdFeB magnetic powder;
[0009] (3) adding the first modified NdFeB magnetic powder obtained in step (1) and the second modified NdFeB magnetic powder obtained in step (2) into an organic solvent medium containing a modifier, and ultrasonically dispersing and stirring the modifier so that the modifier is connected to the first modified NdFeB magnetic powder and the second modified NdFeB magnetic powder through chemical bonds;
[0010] (4) further adding unsaturated monomer and initiator, ultrasonically dispersing and stirring, so that the unsaturated monomer and the modifier undergo a grafting reaction, and the unsaturated monomer undergoes a polymerization reaction to form a coating layer, thereby obtaining a finished product.
[0011] Preferably, the first nano-NdFeB magnetic powder is 50 parts by weight, the nano-silver powder is 1-2 parts by weight, the nano-aluminum powder is 0.5-1 parts by weight, the first solvent is anhydrous ethanol, and the solid content of the first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in the first solvent is 0.8-1g / ml; the amount of the first concentrated ammonia water added is 8-10% of the volume of the first solvent; the amount of the first tetraethyl orthosilicate added is 4-5% of the volume of the first solvent; the reaction temperature is 35-40°C, and the reaction time is 5-10h.
[0012] Preferably, the second nano-NdFeB magnetic powder is 50 parts by weight, the nano-zinc powder is 1-2 parts by weight, the nano-copper powder is 0.5-1 parts by weight, the second solvent is anhydrous ethanol, and the solid content of the second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in the second solvent is 0.8-1g / ml; the amount of the second concentrated ammonia water added is 8-10% of the volume of the second solvent; the amount of the second tetraethyl orthosilicate added is 4-5% of the volume of the second solvent; the reaction temperature is 35-40°C, and the reaction time is 5-10h.
[0013] Preferably, the modifier is a silane coupling agent containing a carbon-carbon double bond, the volume ratio of the magnetic powder mass to the organic solvent is 50-55 g / 100 ml, and the concentration of the modifier is 4-5 wt %.
[0014] Preferably, the unsaturated monomer is at least one of an acrylic unsaturated monomer and an aromatic unsaturated monomer, and the mass ratio of the unsaturated monomer to the magnetic powder is 6 to 8:100.
[0015] Preferably, in step (3), the stirring speed is 400-500 r / min, and the stirring time is 15-20 min.
[0016] Preferably, in step (4), the stirring speed is 80-90 r / min, the temperature is raised to 70-75° C., and the polymerization reaction is carried out for 4-5 hours under a protective atmosphere.
[0017] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:
[0018] By first preparing a first modified NdFeB magnetic powder and a second modified NdFeB magnetic powder, and then mixing the first modified NdFeB magnetic powder and the second modified NdFeB magnetic powder for further modification, the two modifications are organically combined, so that the prepared permanent magnet has a larger remanence and magnetic energy product, and the coercive force is also effectively improved, and the demagnetization rate is greatly reduced to meet the needs of use. DETAILED DESCRIPTION
[0019] The present invention discloses a method for preparing modified NdFeB magnetic powder, comprising the following steps:
[0020] (1) Dispersing first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in a first solvent, adding first concentrated ammonia water and first tetraethyl orthosilicate to react, and obtaining first modified NdFeB magnetic powder; the first nano-NdFeB magnetic powder is 50 parts by weight, the nano-silver powder is 1-2 parts by weight, the nano-aluminum powder is 0.5-1 parts by weight, the first solvent is anhydrous ethanol, and the solid content of the first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in the first solvent is 0.8-1g / ml; the amount of the first concentrated ammonia water added is 8-10% by volume of the first solvent; the amount of the first tetraethyl orthosilicate added is 4-5% by volume of the first solvent; the reaction temperature is 35-40°C, and the reaction time is 5-10h.
[0021] (2) Dispersing a second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in a second solvent, adding a second concentrated ammonia water and a second tetraethyl orthosilicate to react, to obtain a second modified NdFeB magnetic powder; the second nano-NdFeB magnetic powder is 50 parts by weight, the nano-zinc powder is 1-2 parts by weight, the nano-copper powder is 0.5-1 parts by weight, the second solvent is anhydrous ethanol, and the solid content of the second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in the second solvent is 0.8-1g / ml; the amount of the second concentrated ammonia water added is 8-10% by volume of the second solvent; the amount of the second tetraethyl orthosilicate added is 4-5% by volume of the second solvent; the reaction temperature is 35-40°C, and the reaction time is 5-10h.
[0022] (3) adding the first modified NdFeB magnetic powder obtained in step (1) and the second modified NdFeB magnetic powder obtained in step (2) to an organic solvent medium containing a modifier, dispersing and stirring by ultrasonic, so that the modifier is connected to the first modified NdFeB magnetic powder and the second modified NdFeB magnetic powder through chemical bonds; the modifier is a silane coupling agent containing a carbon-carbon double bond, the volume ratio of the magnetic powder mass to the organic solvent is 50-55g / 100ml, the concentration of the modifier is 4-5wt%, the stirring speed is 400-500r / min, and the stirring time is 15-20min.
[0023] (4) Further adding unsaturated monomer and initiator, ultrasonically dispersing and stirring, so that the unsaturated monomer and the modifier undergo grafting reaction, and the unsaturated monomer undergoes polymerization reaction to form a coating layer to obtain a finished product. The unsaturated monomer is at least one of an acrylic unsaturated monomer and an aromatic unsaturated monomer, and the mass ratio of the unsaturated monomer to the magnetic powder is 6 to 8:100. The stirring speed is 80 to 90 r / min, the temperature is raised to 70 to 75° C., and the polymerization reaction is carried out for 4 to 5 hours under a protective atmosphere.
[0024] The present invention is further described in detail with multiple embodiments below:
[0025] Embodiment 1:
[0026] A method for preparing modified NdFeB magnetic powder comprises the following steps:
[0027] (1) Dispersing first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in a first solvent, adding first concentrated ammonia water and first tetraethyl orthosilicate to react, to obtain first modified NdFeB magnetic powder; the first nano-NdFeB magnetic powder is 50 parts by weight, the nano-silver powder is 1 part by weight, the nano-aluminum powder is 0.6 parts by weight, the first solvent is anhydrous ethanol, and the solid content of the first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in the first solvent is 0.88g / ml; the amount of the first concentrated ammonia water added is 8.5% by volume of the first solvent; the amount of the first tetraethyl orthosilicate added is 4.2% by volume of the first solvent; the reaction temperature is 36°C, and the reaction time is 6h.
[0028] (2) Dispersing a second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in a second solvent, adding a second concentrated ammonia water and a second tetraethyl orthosilicate to react, to obtain a second modified NdFeB magnetic powder; the second nano-NdFeB magnetic powder is 50 parts by weight, the nano-zinc powder is 1.5 parts by weight, the nano-copper powder is 0.8 parts by weight, the second solvent is anhydrous ethanol, and the solid content of the second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in the second solvent is 0.82 g / ml; the amount of the second concentrated ammonia water added is 8.1% by volume of the second solvent; the amount of the second tetraethyl orthosilicate added is 4.5% by volume of the second solvent; the reaction temperature is 35°C, and the reaction time is 7 hours.
[0029] (3) adding the first modified NdFeB magnetic powder obtained in step (1) and the second modified NdFeB magnetic powder obtained in step (2) to an organic solvent medium containing a modifier, dispersing and stirring by ultrasonic, so that the modifier is connected to the first modified NdFeB magnetic powder and the second modified NdFeB magnetic powder through chemical bonds; the modifier is a silane coupling agent containing a carbon-carbon double bond, the volume ratio of the magnetic powder mass to the organic solvent is 52g / 100ml, and the concentration of the modifier is 4.5wt%. The stirring speed is 400r / min, and the stirring time is 17min.
[0030] (4) Further adding unsaturated monomer and initiator, ultrasonically dispersing and stirring, so that the unsaturated monomer and the modifier undergo grafting reaction, and the unsaturated monomer undergoes polymerization reaction to form a coating layer to obtain a finished product. The unsaturated monomer is an acrylic unsaturated monomer, and the mass ratio of the unsaturated monomer to the magnetic powder is 6:100. The stirring speed is 81r / min, the temperature is raised to 75°C, and the polymerization reaction is carried out for 4h under a protective atmosphere.
[0031] The modified NdFeB magnetic powder prepared in this embodiment is used to make NdFeB permanent magnets by conventional methods. After testing, the prepared NdFeB permanent magnets have a remanence of 20.4 kGs, a magnetic energy product of 61 MGOe, a coercive force of 51000 Oe, and a high temperature demagnetization rate of 0.03% after being placed at 200°C for 1 hour.
[0032] Embodiment 2:
[0033] A method for preparing modified NdFeB magnetic powder comprises the following steps:
[0034] (1) Dispersing first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in a first solvent, adding first concentrated ammonia water and first tetraethyl orthosilicate to react, to obtain first modified NdFeB magnetic powder; the first nano-NdFeB magnetic powder is 50 parts by weight, the nano-silver powder is 2 parts by weight, the nano-aluminum powder is 0.8 parts by weight, the first solvent is anhydrous ethanol, and the solid content of the first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in the first solvent is 0.8g / ml; the amount of the first concentrated ammonia water added is 9% by volume of the first solvent; the amount of the first tetraethyl orthosilicate added is 4.5% by volume of the first solvent; the reaction temperature is 35°C, and the reaction time is 7h.
[0035] (2) Dispersing a second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in a second solvent, adding a second concentrated ammonia water and a second tetraethyl orthosilicate to react, to obtain a second modified NdFeB magnetic powder; the second nano-NdFeB magnetic powder is 50 parts by weight, the nano-zinc powder is 1 part by weight, the nano-copper powder is 0.5 parts by weight, the second solvent is anhydrous ethanol, and the solid content of the second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in the second solvent is 0.91 g / ml; the amount of the second concentrated ammonia water added is 8% by volume of the second solvent; the amount of the second tetraethyl orthosilicate added is 4.8% by volume of the second solvent; the reaction temperature is 37° C., and the reaction time is 8 hours.
[0036] (3) adding the first modified NdFeB magnetic powder obtained in step (1) and the second modified NdFeB magnetic powder obtained in step (2) to an organic solvent medium containing a modifier, dispersing and stirring by ultrasonic, so that the modifier is connected to the first modified NdFeB magnetic powder and the second modified NdFeB magnetic powder through chemical bonds; the modifier is a silane coupling agent containing a carbon-carbon double bond, the volume ratio of the magnetic powder mass to the organic solvent is 50g / 100ml, and the concentration of the modifier is 4wt%. The stirring speed is 430r / min, and the stirring time is 15min.
[0037] (4) Further adding unsaturated monomer and initiator, ultrasonically dispersing and stirring, so that the unsaturated monomer and the modifier undergo grafting reaction, and the unsaturated monomer undergoes polymerization reaction to form a coating layer to obtain a finished product. The unsaturated monomer is an aromatic unsaturated monomer, and the mass ratio of the unsaturated monomer to the magnetic powder is 6.5:100. The stirring speed is 85r / min, the temperature is raised to 70°C, and the polymerization reaction is carried out for 4.5h under a protective atmosphere.
[0038] The modified NdFeB magnetic powder prepared in this embodiment is used to make NdFeB permanent magnets by conventional methods. After testing, the prepared NdFeB permanent magnets have a remanence of 19.4 kGs, a magnetic energy product of 59 MGOe, a coercive force of 49050 Oe, and a high temperature demagnetization rate of 0.04% after being placed at 200°C for 1 hour.
[0039] Embodiment 3:
[0040] A method for preparing modified NdFeB magnetic powder comprises the following steps:
[0041] (1) Dispersing first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in a first solvent, adding first concentrated ammonia water and first tetraethyl orthosilicate to react, to obtain first modified NdFeB magnetic powder; the first nano-NdFeB magnetic powder is 50 parts by weight, the nano-silver powder is 1.5 parts by weight, the nano-aluminum powder is 1 part by weight, the first solvent is anhydrous ethanol, and the solid content of the first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in the first solvent is 0.85g / ml; the amount of the first concentrated ammonia water added is 8% by volume of the first solvent; the amount of the first tetraethyl orthosilicate added is 4% by volume of the first solvent; the reaction temperature is 37°C, and the reaction time is 5h.
[0042] (2) Dispersing a second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in a second solvent, adding a second concentrated ammonia water and a second tetraethyl orthosilicate to react, to obtain a second modified NdFeB magnetic powder; the second nano-NdFeB magnetic powder is 50 parts by weight, the nano-zinc powder is 2 parts by weight, the nano-copper powder is 0.7 parts by weight, the second solvent is anhydrous ethanol, and the solid content of the second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in the second solvent is 0.8 g / ml; the amount of the second concentrated ammonia water added is 9% by volume of the second solvent; the amount of the second tetraethyl orthosilicate added is 4% by volume of the second solvent; the reaction temperature is 39° C., and the reaction time is 10 h.
[0043] (3) adding the first modified NdFeB magnetic powder obtained in step (1) and the second modified NdFeB magnetic powder obtained in step (2) to an organic solvent medium containing a modifier, dispersing and stirring by ultrasonic, so that the modifier is connected to the first modified NdFeB magnetic powder and the second modified NdFeB magnetic powder through chemical bonds; the modifier is a silane coupling agent containing a carbon-carbon double bond, the volume ratio of the magnetic powder mass to the organic solvent is 54 g / 100 ml, and the concentration of the modifier is 5 wt %. The stirring speed is 500 r / min, and the stirring time is 18 min.
[0044] (4) Further adding unsaturated monomer and initiator, ultrasonically dispersing and stirring, so that the unsaturated monomer and the modifier undergo grafting reaction, and the unsaturated monomer undergoes polymerization reaction to form a coating layer to obtain a finished product. The unsaturated monomer is a mixture of acrylic unsaturated monomer and aromatic unsaturated monomer, and the mass ratio of the unsaturated monomer to the magnetic powder is 7:100. The stirring speed is 90r / min, the temperature is raised to 71°C, and the polymerization reaction is carried out for 4.3h under a protective atmosphere.
[0045] The modified NdFeB magnetic powder prepared in this embodiment is used to make NdFeB permanent magnets by conventional methods. After testing, the prepared NdFeB permanent magnets have a remanence of 20.1 kGs, a magnetic energy product of 58 MGOe, a coercive force of 48500 Oe, and a high temperature demagnetization rate of 0.04% after being placed at 200°C for 1 hour.
[0046] Embodiment 4:
[0047] A method for preparing modified NdFeB magnetic powder comprises the following steps:
[0048] (1) Dispersing first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in a first solvent, adding first concentrated ammonia water and first tetraethyl orthosilicate to react, to obtain first modified NdFeB magnetic powder; the first nano-NdFeB magnetic powder is 50 parts by weight, the nano-silver powder is 1.6 parts by weight, the nano-aluminum powder is 0.7 parts by weight, the first solvent is anhydrous ethanol, and the solid content of the first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in the first solvent is 0.9 g / ml; the amount of the first concentrated ammonia water added is 10% by volume of the first solvent; the amount of the first tetraethyl orthosilicate added is 5% by volume of the first solvent; the reaction temperature is 38° C., and the reaction time is 10 hours.
[0049] (2) Dispersing a second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in a second solvent, adding a second concentrated ammonia water and a second tetraethyl orthosilicate to react, to obtain a second modified NdFeB magnetic powder; the second nano-NdFeB magnetic powder is 50 parts by weight, the nano-zinc powder is 1.6 parts by weight, the nano-copper powder is 0.9 parts by weight, the second solvent is anhydrous ethanol, and the solid content of the second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in the second solvent is 1 g / ml; the amount of the second concentrated ammonia water added is 10% by volume of the second solvent; the amount of the second tetraethyl orthosilicate added is 5% by volume of the second solvent; the reaction temperature is 40°C, and the reaction time is 5 hours.
[0050] (3) adding the first modified NdFeB magnetic powder obtained in step (1) and the second modified NdFeB magnetic powder obtained in step (2) to an organic solvent medium containing a modifier, dispersing and stirring by ultrasonic, so that the modifier is connected to the first modified NdFeB magnetic powder and the second modified NdFeB magnetic powder through chemical bonds; the modifier is a silane coupling agent containing a carbon-carbon double bond, the volume ratio of the magnetic powder mass to the organic solvent is 55g / 100ml, and the concentration of the modifier is 4.3wt%. The stirring speed is 480r / min, and the stirring time is 19min.
[0051] (4) Further adding unsaturated monomer and initiator, ultrasonically dispersing and stirring, so that the unsaturated monomer and the modifier undergo grafting reaction, and the unsaturated monomer undergoes polymerization reaction to form a coating layer to obtain a finished product. The unsaturated monomer is an acrylic unsaturated monomer, and the mass ratio of the unsaturated monomer to the magnetic powder is 7.8:100. The stirring speed is 80r / min, the temperature is raised to 73°C, and the polymerization reaction is carried out under a protective atmosphere for 5 hours.
[0052] The modified NdFeB magnetic powder prepared in this embodiment is used to make NdFeB permanent magnets by conventional methods. After testing, the prepared NdFeB permanent magnets have a remanence of 19.5 kGs, a magnetic energy product of 60 MGOe, a coercive force of 49000 Oe, and a high temperature demagnetization rate of 0.05% after being placed at 200°C for 1 hour.
[0053] Embodiment 5:
[0054] A method for preparing modified NdFeB magnetic powder comprises the following steps:
[0055] (1) Dispersing first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in a first solvent, adding first concentrated ammonia water and first tetraethyl orthosilicate to react, to obtain first modified NdFeB magnetic powder; the first nano-NdFeB magnetic powder is 50 parts by weight, the nano-silver powder is 1.8 parts by weight, the nano-aluminum powder is 0.9 parts by weight, the first solvent is anhydrous ethanol, and the solid content of the first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in the first solvent is 1g / ml; the amount of the first concentrated ammonia water added is 9.5% by volume of the first solvent; the amount of the first tetraethyl orthosilicate added is 4.8% by volume of the first solvent; the reaction temperature is 40°C, and the reaction time is 8h.
[0056] (2) Dispersing a second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in a second solvent, adding a second concentrated ammonia water and a second tetraethyl orthosilicate to react, to obtain a second modified NdFeB magnetic powder; the second nano-NdFeB magnetic powder is 50 parts by weight, the nano-zinc powder is 1.8 parts by weight, the nano-copper powder is 1 part by weight, the second solvent is anhydrous ethanol, and the solid content of the second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in the second solvent is 0.85 g / ml; the amount of the second concentrated ammonia water added is 8.8% by volume of the second solvent; the amount of the second tetraethyl orthosilicate added is 4.3% by volume of the second solvent; the reaction temperature is 36°C, and the reaction time is 6 hours.
[0057] (3) adding the first modified NdFeB magnetic powder obtained in step (1) and the second modified NdFeB magnetic powder obtained in step (2) to an organic solvent medium containing a modifier, dispersing and stirring by ultrasonic, so that the modifier is connected to the first modified NdFeB magnetic powder and the second modified NdFeB magnetic powder through chemical bonds; the modifier is a silane coupling agent containing a carbon-carbon double bond, the volume ratio of the magnetic powder mass to the organic solvent is 53 g / 100 ml, and the concentration of the modifier is 4.8 wt %. The stirring speed is 460 r / min, and the stirring time is 20 min.
[0058] (4) Further adding unsaturated monomer and initiator, ultrasonically dispersing and stirring, so that the unsaturated monomer and the modifier undergo grafting reaction, and the unsaturated monomer undergoes polymerization reaction to form a coating layer to obtain a finished product. The unsaturated monomer is an aromatic unsaturated monomer, and the mass ratio of the unsaturated monomer to the magnetic powder is 8:100. The stirring speed is 86 r / min, the temperature is raised to 72° C., and the polymerization reaction is carried out for 4.5 hours under a protective atmosphere.
[0059] The modified NdFeB magnetic powder prepared in this embodiment is used to make NdFeB permanent magnets by conventional methods. After testing, the prepared NdFeB permanent magnets have a remanence of 19.8 kGs, a magnetic energy product of 58 MGOe, a coercive force of 47800 Oe, and a high temperature demagnetization rate of 0.05% after being placed at 200°C for 1 hour.
[0060] Embodiment 6:
[0061] A method for preparing modified NdFeB magnetic powder comprises the following steps:
[0062] (1) Dispersing first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in a first solvent, adding first concentrated ammonia water and first tetraethyl orthosilicate to react, to obtain first modified NdFeB magnetic powder; the first nano-NdFeB magnetic powder is 50 parts by weight, the nano-silver powder is 1.3 parts by weight, the nano-aluminum powder is 0.5 parts by weight, the first solvent is anhydrous ethanol, and the solid content of the first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in the first solvent is 0.95g / ml; the amount of the first concentrated ammonia water added is 9.8% by volume of the first solvent; the amount of the first tetraethyl orthosilicate added is 4.4% by volume of the first solvent; the reaction temperature is 39°C, and the reaction time is 9h.
[0063] (2) Dispersing a second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in a second solvent, adding a second concentrated ammonia water and a second tetraethyl orthosilicate to react, to obtain a second modified NdFeB magnetic powder; the second nano-NdFeB magnetic powder is 50 parts by weight, the nano-zinc powder is 1.7 parts by weight, the nano-copper powder is 0.6 parts by weight, the second solvent is anhydrous ethanol, and the solid content of the second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in the second solvent is 0.95 g / ml; the amount of the second concentrated ammonia water added is 9.5% by volume of the second solvent; the amount of the second tetraethyl orthosilicate added is 4.1% by volume of the second solvent; the reaction temperature is 38°C, and the reaction time is 9 hours.
[0064] (3) adding the first modified NdFeB magnetic powder obtained in step (1) and the second modified NdFeB magnetic powder obtained in step (2) to an organic solvent medium containing a modifier, dispersing and stirring by ultrasonic, so that the modifier is connected to the first modified NdFeB magnetic powder and the second modified NdFeB magnetic powder through chemical bonds; the modifier is a silane coupling agent containing a carbon-carbon double bond, the volume ratio of the magnetic powder mass to the organic solvent is 51 g / 100 ml, and the concentration of the modifier is 4.9 wt %. The stirring speed is 470 r / min, and the stirring time is 16 min.
[0065] (4) Further adding unsaturated monomer and initiator, ultrasonically dispersing and stirring, so that the unsaturated monomer and the modifier undergo grafting reaction, and the unsaturated monomer undergoes polymerization reaction to form a coating layer to obtain a finished product. The unsaturated monomer is an acrylic unsaturated monomer, and the mass ratio of the unsaturated monomer to the magnetic powder is 7.4:100. The stirring speed is 88r / min, the temperature is raised to 74°C, and the polymerization reaction is carried out for 4.8h under a protective atmosphere.
[0066] The modified NdFeB magnetic powder prepared in this embodiment is used to make NdFeB permanent magnets by conventional methods. After testing, the prepared NdFeB permanent magnets have a remanence of 18.8 kGs, a magnetic energy product of 60 MGOe, a coercive force of 49000 Oe, and a high temperature demagnetization rate of 0.04% after being placed at 200°C for 1 hour.
[0067] The design focus of the present invention is: by first preparing a first modified NdFeB magnetic powder and a second modified NdFeB magnetic powder, and then mixing the first modified NdFeB magnetic powder and the second modified NdFeB magnetic powder for further modification, the two modifications are organically combined, so that the prepared permanent magnet has a larger remanence and magnetic energy product, and the coercive force is also effectively improved, and the demagnetization rate is greatly reduced to meet the needs of use.
[0068] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.
Claims
1. A method for preparing modified NdFeB magnetic powder, characterized in that: The following steps are included: (1) dispersing a first nano-NdFeB magnetic powder, a nano-silver powder and a nano-aluminum powder in a first solvent, adding a first concentrated ammonia solution and a first tetraethyl orthosilicate to react, thereby obtaining a first modified NdFeB magnetic powder; (2) dispersing a second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in a second solvent, adding a second concentrated ammonia solution and a second tetraethyl orthosilicate to react, thereby obtaining a second modified NdFeB magnetic powder; (3) adding the first modified NdFeB magnetic powder obtained in step (1) and the second modified NdFeB magnetic powder obtained in step (2) into an organic solvent medium containing a modifier, and ultrasonically dispersing and stirring the modifier so that the modifier is connected to the first modified NdFeB magnetic powder and the second modified NdFeB magnetic powder through chemical bonds; (4) further adding unsaturated monomers and initiators, ultrasonically dispersing and stirring, so that the unsaturated monomers and the modifiers undergo a grafting reaction, and the unsaturated monomers undergo a polymerization reaction to form a coating layer, thereby obtaining a finished product; The modifier is a silane coupling agent containing a carbon-carbon double bond, the volume ratio of the magnetic powder mass to the organic solvent is 50-55g / 100ml, and the concentration of the modifier is 4-5wt%; the unsaturated monomer is at least one of an acrylic unsaturated monomer and an aromatic unsaturated monomer, and the mass ratio of the unsaturated monomer to the magnetic powder is 6-8:
100.
2. The method for preparing modified NdFeB magnetic powder according to claim 1, characterized in that: The first nano-NdFeB magnetic powder is 50 parts by weight, the nano-silver powder is 1-2 parts by weight, the nano-aluminum powder is 0.5-1 parts by weight, the first solvent is anhydrous ethanol, and the solid content of the first nano-NdFeB magnetic powder, nano-silver powder and nano-aluminum powder in the first solvent is 0.8-1g / ml; the amount of the first concentrated ammonia water added is 8-10% of the volume of the first solvent; the amount of the first tetraethyl orthosilicate added is 4-5% of the volume of the first solvent; the reaction temperature is 35-40°C, and the reaction time is 5-10h.
3. The method for preparing modified NdFeB magnetic powder according to claim 1, characterized in that: The second nano-NdFeB magnetic powder is 50 parts by weight, the nano-zinc powder is 1-2 parts by weight, the nano-copper powder is 0.5-1 parts by weight, the second solvent is anhydrous ethanol, and the solid content of the second nano-NdFeB magnetic powder, nano-zinc powder and nano-copper powder in the second solvent is 0.8-1g / ml; the amount of the second concentrated ammonia water added is 8-10% of the volume of the second solvent; the amount of the second tetraethyl orthosilicate added is 4-5% of the volume of the second solvent; the reaction temperature is 35-40°C, and the reaction time is 5-10h.
4. The method for preparing modified NdFeB magnetic powder according to claim 1, characterized in that: In the step (3), the stirring speed is 400-500 r / min and the stirring time is 15-20 min.
5. The method for preparing modified NdFeB magnetic powder according to claim 1, characterized in that: In the step (4), the stirring speed is 80-90 r / min, the temperature is raised to 70-75° C., and the polymerization reaction is carried out for 4-5 hours under a protective atmosphere.
Citation Information
Patent Citations
Method for preparing composite sintered neodymium-iron-boron permanent magnet material added with gadolinium, holmium and yttrium
CN102956336A
Method for dysprosium infiltration of NdFeB magnets
CN105489336A